2018
DOI: 10.1038/s41598-018-19774-4
|View full text |Cite
|
Sign up to set email alerts
|

Production of Wilson Disease Model Rabbits with Homology-Directed Precision Point Mutations in the ATP7B Gene Using the CRISPR/Cas9 System

Abstract: CRISPR/Cas9 has recently been developed as an efficient genome engineering tool. The rabbit is a suitable animal model for studies of metabolic diseases. In this study, we generated ATP7B site-directed point mutation rabbits to simulate a major mutation type in Asians (p. Arg778Leu) with Wilson disease (WD) by using the CRISPR/Cas9 system combined with single-strand DNA oligonucleotides (ssODNs). The efficiency of the precision point mutation was 52.94% when zygotes were injected 14 hours after HCG treatment a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 49 publications
0
14
0
1
Order By: Relevance
“…Wu et al () also reported that p.R778L homozygous patients had early onset of hepatic damage. WD rabbit model homozygous for p.R778L died of severe hepatic damage at 3 months of age (Jiang et al, ). In vitro investigation revealed that the R778L mutation may disrupt the subcellular localization and trafficking of the ATP7B protein, reducing copper excretion, and resulting in copper accumulation (Zhu, Dong, Ni, & Wu, ).…”
Section: Discussionmentioning
confidence: 99%
“…Wu et al () also reported that p.R778L homozygous patients had early onset of hepatic damage. WD rabbit model homozygous for p.R778L died of severe hepatic damage at 3 months of age (Jiang et al, ). In vitro investigation revealed that the R778L mutation may disrupt the subcellular localization and trafficking of the ATP7B protein, reducing copper excretion, and resulting in copper accumulation (Zhu, Dong, Ni, & Wu, ).…”
Section: Discussionmentioning
confidence: 99%
“…[205][206][207] Other studies have utilized endonucleases to generate different kinds of immunodeficient animal models that were previously unable to be established due to a lack of effective genetic modification. [207][208][209][210] As a result of engineered nucleasemediated editing of genomic modifications, other animal disease models have been developed, simulating Rett syndrome, 211 hereditary deafness, 212 Wilson disease, 213 Laron syndrome, 214 Niemann-Pick disease, 215 Netherton syndrome, 216 and so on. Advances in genome editing technologies will further expand the application of animal models in disease mechanism research and treatment development.…”
Section: Other Hereditary Diseasesmentioning
confidence: 99%
“…58,59 Wilson disease Jiang et al created precision point mutations, using CRISPR technology in rabbits, to develop a model of Wilson disease (WD). 60 WD is an autosomal recessive genetic disorder caused by mutations in the membrane copper transporter gene, ATP7B. 61,62 The authors targeted the Atp7b gene with sgRNAs and provided a single-stranded donor oligonucleotide template for homology-directed repair, to obtain the missense mutation Arg778Leu, a common disease mutation in Asian populations.…”
Section: Hereditary Tyrosinemia Type Imentioning
confidence: 99%
“…61,62 The authors targeted the Atp7b gene with sgRNAs and provided a single-stranded donor oligonucleotide template for homology-directed repair, to obtain the missense mutation Arg778Leu, a common disease mutation in Asian populations. 60 When comparing zygotes obtained from donor rabbits 14 h or 19 h after human chorionic gonadotropin treatment, the authors found that injections performed in pronuclear embryos at earlier stages resulted in higher rates of point mutation (over 50%) and reduced gene knockout. Atp7b mutant rabbits exhibited copper accumulation in the liver and kidney, as observed in human WD, and died at an early age of 3 months.…”
Section: Hereditary Tyrosinemia Type Imentioning
confidence: 99%